2014
DOI: 10.1002/hep.27201
|View full text |Cite
|
Sign up to set email alerts
|

Benzyl alcohol attenuates acetaminophen-induced acute liver injury in a Toll-like receptor-4-dependent pattern in mice

Abstract: Acetaminophen (APAP) toxicity is the most common cause of acute liver failure in industrialized countries. Understanding the mechanisms of APAP‐induced liver injury as well as other forms of sterile liver injury is critical to improve the care of patients. Recent studies demonstrate that danger signaling and inflammasome activation play a role in APAP‐induced injury. The aim of these investigations was to test the hypothesis that benzyl alcohol (BA) is a therapeutic agent that protects against APAP‐induced liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 39 publications
(59 reference statements)
5
49
0
Order By: Relevance
“…There are already reports demonstrate that TLR3 and TLR4 play critical roles in the progression of AP-induced hepatotoxicity [26,27]. In addition, there is report that benzyl alcohol attenuates AP-induced liver injury in a TLR4-dependent pattern in mice [28]. In the present study, CGA was found to inhibit AP-induced the activation of TLR3 and TLR4, which indicating that CGA may attenuate AP-induced hepatotoxicity via inhibiting TLR3 and TLR4.…”
Section: Discussionsupporting
confidence: 46%
“…There are already reports demonstrate that TLR3 and TLR4 play critical roles in the progression of AP-induced hepatotoxicity [26,27]. In addition, there is report that benzyl alcohol attenuates AP-induced liver injury in a TLR4-dependent pattern in mice [28]. In the present study, CGA was found to inhibit AP-induced the activation of TLR3 and TLR4, which indicating that CGA may attenuate AP-induced hepatotoxicity via inhibiting TLR3 and TLR4.…”
Section: Discussionsupporting
confidence: 46%
“…Elevated levels of HMGB-1 were also observed in the liver biopsy samples from human alcoholic individuals compared to normal subjects . Elevated release of HMGB-1 and damage signaling were also observed in HFDexposed rats , APAP-induced DILI (Cai et al, 2014), and I/R injury (Kamo et al, 2013), although a few exceptions exist. For instance, one report indicated that hepatocyte-specific deletion of HMGB-1 worsens I/R liver injury , suggesting that HMGB-1 may play a dual role in regulating the cellular immune function, depending on the cellular context.…”
Section: Role and Regulation Of Cyp2e1 In Liver Diseasementioning
confidence: 95%
“…IL-1β is a pro-inflammatory cytokine that plays a critical role in the development of hepatic failure [10]. IL-1β is produced as an inactivate form named as pro-IL-1β [11].…”
Section: Introductionmentioning
confidence: 99%